STUDY ON RELIABILITY OF PHOTOELECTRIC PCB UNDER THERMAL CYCLE - CHENG Lei; ZHOU DeJian; WU ZhaoHua (Jixie qiangdu)
The influence of thermal cycle loading on optoelectronic PCB（Printed Circuit Board） reliability was presented.In product conceptual design stage,the three-dimensional finite element model of photoelectric PCB was established.The finite element analysis was carried out under thermal cycle loading which defined by GJB 150.5-86.The influence includes solder joints reliability of optoelectronic PCB,optical coupling efficiency and optical fiber reliability.The following results are obtained.First,the maximum stress of solder joint and optical fiber ribbon is in the security range and the structure is not destroyed.Second,photoelectric coupling efficiency is not changed significantly,which guarantees the stability of the optical transmission.It proves the feasibility of the design scheme and promotes the engineering applications of photoelectric interconnection technology.